The Influence of Financial Literacy, Financial Technology, and Risk Perception on Investment Decisions - Roshinta, Maudy; Ilham Wardhana Haeruddin, Muhammad; Nurman, Nurman; Ichwan Musa, Muh; Ruma, Zainal (El-kahfi | Jurnal Ekonomi Islam, 2025)
This study investigates the influence of financial literacy, financial technology, and risk perception on investment decision-making among users of the Pegadaian Digital application in Makassar, Indonesia. Employing an explanatory quantitative research design, data were collected through online questionnaires distributed to a sample of 60 respondents. The analysis involved instrument validity and reliability testing, classical assumption tests, and hypothesis testing, all conducted using IBM SPSS 25. The findings reveal that, partially, financial literacy and risk perception exert a positive and statistically significant effect on investment decisions, whereas financial technology demonstrates a negative and statistically insignificant effect. However, when considered simultaneously, financial literacy, financial technology, and risk perception collectively exert a significant influence on investment decisions. These results highlight the importance of financial literacy and risk awareness in shaping investors’ behavior and decision-making processes. The study further suggests that prospective and current investors should deepen their knowledge and understanding of available investment instruments to make informed decisions, reduce uncertainty, and minimize potential losses.